2015
DOI: 10.1039/c5ra13184g
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of red emission from upconversion nanoparticles via surface plasmon-coupled emission

Abstract: Upconversion nanoparticle and gold nanorod heteronanostructures spaced by a polyelectrolyte are prepared by a layer-by-layer assembly process to enhance red emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…An intense red emission band around 660 nm and a very weak green emission band ≈550 nm could be identified in the spectrum as shown in Figure d, which were attributed to the 4 F 9/2 → 4 I 15/2 and the 2 H 11/2, 4 S 3/2 → 4 I 15/2 transitions of Er 3+ ion (Figure e), respectively. Many previous studies on the plasmonic enhancement UCL of Yb 3+ and Er 3+ coactivated hexagonal NaYF 4 nanocrystals have indicated that the enhancement factor was not equal for green and red emissions but varied strongly with different characteristics of plasmonic structures . Furthermore, a fraction of red UCL in Yb 3+ /Er 3+ codoped NaYF 4 nanocrystals originates from the excited state nonradiative relaxation of the green UCL ( 4 S 3/2 level) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An intense red emission band around 660 nm and a very weak green emission band ≈550 nm could be identified in the spectrum as shown in Figure d, which were attributed to the 4 F 9/2 → 4 I 15/2 and the 2 H 11/2, 4 S 3/2 → 4 I 15/2 transitions of Er 3+ ion (Figure e), respectively. Many previous studies on the plasmonic enhancement UCL of Yb 3+ and Er 3+ coactivated hexagonal NaYF 4 nanocrystals have indicated that the enhancement factor was not equal for green and red emissions but varied strongly with different characteristics of plasmonic structures . Furthermore, a fraction of red UCL in Yb 3+ /Er 3+ codoped NaYF 4 nanocrystals originates from the excited state nonradiative relaxation of the green UCL ( 4 S 3/2 level) .…”
Section: Resultsmentioning
confidence: 99%
“…This localization results in the near‐field enhancement by orders of magnitude and can be used to greatly promote photochemical reactions and amplify the luminescence from nearby optical emitters as extensively demonstrated in plasmonic‐enhanced fluorescence of semiconductor quantum dots and dye molecules . This strategy has also been extended to enhance the UCL of UCNPs with metallic nanoparticles, structured metallic surfaces, metal shell architectures, and metallic tip …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There have been two main strategies to enhance the upconversion efficiency, which is either by modifying the upconverting materials or by tailoring the electromagnetic field with plasmonic nanostructures close to the UCNP's surface, improving its absorption (more than 100×) and/or emission (up to 20×) . Previous investigations involve UCNPs in close proximity to metallic nanostructures and nanoarrays, such as nanospheres, nanorods, nanoparticle islands, nanocrescents, gold pillars, disk‐coupled dots‐on‐pillar arrays, nanocavity arrays, and nanocaps . In these ensemble studies, increased emission of up to 300‐fold was observed by Zhang et al Direct evidence of plasmonic‐enhanced upconversion luminescence has been provided at the single particle level, where one UCNP is coupled to an individual plasmonic nanostructure or coated with noble metals offering fluorescence enhancements of up to 48‐fold .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detection of a biological sample is difficult when the excitation volume is very limited as in for SMD so that the number of fluorophores that radiate is less. The pursuit of increasing the SPCE light intensity is an active area of research [14][15][16][17][18][19]. Two approaches are usually used to increase the SPCE light intensity: First, by increasing the radiation of the fluorophores, and second, by increasing the coupling of the radiation of the fluorophores to SPCE.…”
Section: Introductionmentioning
confidence: 99%